2015
DOI: 10.1002/jsid.378
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and visual performance in stereoscopic displays: A review

Abstract: In this paper, authors systematically selected and reviewed articles related to stereoscopic displays and their advances, with a special focus on perception, interaction, and corresponding challenges. The aim was to understand interaction‐related problems, provide possible explanations, and identify factors that limit their applications. Despite promising advancements, there are still issues that researchers in the field fail to explain precisely. The two major problems in stereoscopic viewing are, compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 106 publications
4
32
0
Order By: Relevance
“…Even within this distance range, we found that the overall position judgment accuracy dropped sharply from 0.91 (at 65 cm) to 0.77 (at 150 cm) in the stereoscopic displays. While there are differences between those studies and this one, the results are consistent where the ratio of accuracies in the frontal plane of virtual and real environments were better (0.81/0.88 = 92%, in Geuss et al and 0.85/0.94 = 90%, in the present study) when compared with egocentric distance perception in the depth plane (50–80% of the actual).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Even within this distance range, we found that the overall position judgment accuracy dropped sharply from 0.91 (at 65 cm) to 0.77 (at 150 cm) in the stereoscopic displays. While there are differences between those studies and this one, the results are consistent where the ratio of accuracies in the frontal plane of virtual and real environments were better (0.81/0.88 = 92%, in Geuss et al and 0.85/0.94 = 90%, in the present study) when compared with egocentric distance perception in the depth plane (50–80% of the actual).…”
Section: Discussionsupporting
confidence: 78%
“…Following the overall underestimation of distance in the virtual environment in both egocentric and exocentric distance spaces, one may expect that the compression could be volumetric . The results by Lin et al and Lin et al showed a significant effect of parallax on a center‐to‐center distance between mixed real and virtual targets and between two virtual targets, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The current generation of VR headsets still yield a modest field of view of 90°–100° horizontally, which although is far less than the human binocular field of view of 220°, is still far greater than the angular coverage of the normal use‐case of any direct‐view display. Even though VR displays feature impressive pixel counts, the perceived pixel density is still much worse than conventional monitors …”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…Understanding movement performances and behaviors depicted by the stereoscopic environment and then comparing it with the real world performances and movement behaviors, would help to explain the space perception issues reported in various studies (C. J. Lin & Woldegiorgis, 2015;Renner et al, 2013). …”
Section: Introductionmentioning
confidence: 99%